2011
DOI: 10.5194/acp-11-8459-2011
|View full text |Cite
|
Sign up to set email alerts
|

Minor effect of physical size sorting on iron solubility of transported mineral dust

Abstract: Abstract.Observations show that the fractional solubility of Fe (FS-Fe, percentage of dissolved to total Fe) in dust aerosol increases considerably from 0.1 % in regions of high dust mass concentration to 80 % in remote regions where concentrations are low. Here, we combined laboratory geochemical measurements with global aerosol model simulations to test the hypothesis that the increase in FS-Fe is due to physical size sorting during transport. We determined the FS-Fe and fractional solubility of Al (FS-Al) i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 69 publications
(106 reference statements)
4
40
0
Order By: Relevance
“…In addition, the dust-derived Fe supply to low-nitrate low-chlorophyll (LNLC) regions of the oceans has been shown to control dinitrogen fixation (Moore et al, 2009;Schlosser et al, 2014). Therefore, interest has grown in recent years regarding atmospheric aerosol transport, inputs to the surface ocean, and the subsequent dissolution of Fe from aerosols (Desboeufs et al, 2001;Jickells and Spokes, 2001;Hand et al, 2004;Guieu et al, 2005;Meskhidze et al, 2005;Baker and Jickells, 2006;Buck et al, 2006Buck et al, , 2010Cwiertny et al, 2008;Journet et al, 2008;Mahowald et al, 2009;Shi et al, 2009Shi et al, , 2011Aguilar-Islas et al, 2010;Baker and Croot, 2010;Fu et al, 2010;Johnson et al, 2010;Paris et al, 2010;Trapp et al, 2010;Formenti et al, 2011;Rubin et al, 2011;Takahashi et al, 2011;Sholkovitz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the dust-derived Fe supply to low-nitrate low-chlorophyll (LNLC) regions of the oceans has been shown to control dinitrogen fixation (Moore et al, 2009;Schlosser et al, 2014). Therefore, interest has grown in recent years regarding atmospheric aerosol transport, inputs to the surface ocean, and the subsequent dissolution of Fe from aerosols (Desboeufs et al, 2001;Jickells and Spokes, 2001;Hand et al, 2004;Guieu et al, 2005;Meskhidze et al, 2005;Baker and Jickells, 2006;Buck et al, 2006Buck et al, , 2010Cwiertny et al, 2008;Journet et al, 2008;Mahowald et al, 2009;Shi et al, 2009Shi et al, , 2011Aguilar-Islas et al, 2010;Baker and Croot, 2010;Fu et al, 2010;Johnson et al, 2010;Paris et al, 2010;Trapp et al, 2010;Formenti et al, 2011;Rubin et al, 2011;Takahashi et al, 2011;Sholkovitz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Iron dissolution from aerosols has been represented by fractional Fe solubility ( %FeS), and varies strongly depending on the aerosol source Sholkovitz et al, 2012). Sholkovitz et al (2012) compiled total Fe loading (Fe T ) and %FeS for a global-scale set of aerosol samples, and found a hyperbolic trend in the %FeS as a function of Fe T , which was explained by the mixing of mineral dusts of high Fe T and low %FeS and anthropogenic aerosols of low Fe T and high %FeS. However, mineral dust is an important supply of bioavailable Fe to the remote ocean, particularly during dust events originating from desert sources.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, large concentrations of aeolian emissions could lead to problems in transport operations (Baddock et al, 2013). Mineral dust deposition on the ocean surface represents an input of micronutrients and, as a consequence, partially controls the productivity of marine ecosystems (Shi et al, 2011). A detailed list of environmental consequences and hazards to human population caused by dust storms, as well as an excellent review of causes and effects of dust storms, can be found in Goudie and Middleton (2006).…”
Section: Introductionmentioning
confidence: 99%
“…The MOUDI samples were then extracted using HF and HNO 3 as described in Shi et al (2011). To extract the total element fraction, the samples were placed in Teflon bombs and HF and HNO 3 were added (1:3) and the bombs were heated for 24 hours at 150°C.…”
Section: Mass and Chemical Analysismentioning
confidence: 99%